Family Support Related to Information, Comfort, Economy and Spiritual in Preeclamptic Pregnancy Care: Qualitative Exploration - Uswatun Insani; Evi Supriatun (University of Muhammadiyah Malang, 2021)
Introduction: Preeclampsia is emergencies in obstetrics, where pregnant women experience health conditions that can be life-threatening and can occur during pregnancy, natal and post-natal. If this obstetric emergency is not treated immediately, it can result in death the mother and also the fetus. Understanding care needs of pregnant with preeclampsia is very important for families because most pregnant women and their families lack understanding and information about high-risk pregnancy care for this disease. Objectives: This research aims to explore the needs of families in the care of preeclampsia. Methods: This research used qualitative descriptive to obtain answers related to individual opinions, responses and perceptions with exploring family needs for care pregnant with preeclampsia. Results: The results of this research there are seven themes related to family needs in pregnancy care with preeclampsia, namely: 1) Description of family knowledge about pregnant with preeclampsia, 2) Information needs, 3) Comfort needs, 4) Economic / financial needs, 5) Spiritual needs, 6) Needs for support from other family members, 7) Need for support from health workers. Conclusions: The importance of involvement of the family and surrounding environment, as a source of strength for pregnant with preeclampsia allows better care for mothers, their babies and reduces the consequences of advanced preeclampsia. Health workers are expected to be able to involve families in the care of pregnant women with preeclampsia as a promotional, preventive and curative effort. 1) Description of family knowledge about pregnant with preeclampsia, 2) Information needs, 3) Comfort needs, 4) Economic / financial needs, 5) Spiritual needs, 6) Needs for support from other family members, 7) Need for support from health workers. Conclusions: The importance of involvement of the family and surrounding environment, as a source of strength for pregnant with preeclampsia allows better care for mothers, their babies and reduces the consequences of advanced preeclampsia. Health workers are expected to be able to involve families in the care of pregnant women with preeclampsia as a promotional, preventive and curative effort. 1) Description of family knowledge about pregnant with preeclampsia, 2) Information needs, 3) Comfort needs, 4) Economic / financial needs, 5) Spiritual needs, 6) Needs for support from other family members, 7) Need for support from health workers. Conclusions: The importance of involvement of the family and surrounding environment, as a source of strength for pregnant with preeclampsia allows better care for mothers, their babies and reduces the consequences of advanced preeclampsia. Health workers are expected to be able to involve families in the care of pregnant women with preeclampsia as a promotional, preventive and curative effort.